Digital Marketing Strategies of MSMEs in Facing Consumption Trends in the New Year - Nugrahini Susantinah Wisnujati; Marjuki; Abdul Razak Munir (Jurnal Minfo Polgan, 2023)
In the era of rapid digital transformation, micro, small, and medium enterprises (MSMEs) play a crucial role in supporting global economic growth. As drivers of the local economy, MSMEs must be able to adapt to changing consumption trends with the onset of the new year. This research aims to delve deeper into the digital marketing strategies employed by MSMEs in facing consumption trends at the beginning of the new year. The study utilizes an extensive review of existing literature, employing qualitative analysis to gain a comprehensive understanding of the subject, spanning the period from 2020 to 2023. The study's findings indicate that in addressing the evolving dynamics of consumption in the new year, digital marketing strategies have proven to be key to the success of Micro, Small, and Medium Enterprises (MSMEs). By crafting adaptive strategies, enhancing personalization, and integrating the latest technologies, MSMEs can confidently face challenges and enhance their competitiveness in the competitive digital market.